Assessment of treatment strategies for stage I non-small cell lung cancer in patients with comorbidities. (August 2022) - Sigel, Keith; Yin Kong, Chung; Leiter, Amanda; Kale, Minal; Mhango, Grace; Huang, Brian; Gould, Michael K.; Wisnivesky, Juan
Highlights: The optimal treatment for stage I non-small cell lung cancer (NSCLC) in patients with oco comorbidities is not known. In a decision analysis treatments for lung cancer that maximized quality adjusted life expectancy differed by comorbidity status, age, sex and tumor size. Some Some patient groups derive maximal benefits from less invasive treatments, particularly those with multiple major comorbid conditions. Abstract: Introduction: Non-small cell lung cancer (NSCLC) patients frequently have major comorbidities but there is scarce data regarding the impact of these conditions on management strategies. We used simulation modeling to compare different treatments for stage I NSCLC for patients with common major comorbidities. Methods: We used data on NSCLC patinet outcomes and quality of life from: (1) the Surveillance Epidemiology and End Results (SEER) database linked to Medicare claims; (2) Kaiser Permanente Southern California electronic health records; and (3) SEER-Medical Health Outcomes Survey to parameterize a novel simulation model of management and outcomes for stage I NSCLC. Relative efficacy of treatment modalities (lobectomy, segmentectomy, wedge resection and stereotactic body radiotherapy [SBRT]) was collected from existing literature and combined using evidence synthesis methods. We then simulated multiple randomized trials comparing these treatments in a variety of scenarios, estimating quality adjusted life expectancy (QALE) according to age, tumor size, histologic subtype, and comorbidity status. Results: Lobectomy and segmentectomy yielded the greatest QALE gains among all simulated age, tumor size and comorbidity groups. Optimal treatment strategies differed by patient sex and age; wedge resection was among the optimal strategies for women aged 80–84 with tumors 0–2 cm in size. SBRT was included in some optimal strategies for patients aged 80–84 with multimorbidity. Conclusions: In simulated comparative trials of four common treatments for stage I NSCLC, aggressive surgical management was typically associated with the greatest projected QALE gains despite the presence of comorbidities, although less aggressive strategies were predicted to be non-inferior in some older comorbid patient groups.